2018
DOI: 10.1111/dar.12665
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐country comparison of proportion of alcohol consumed in harmful drinking occasions using the International Alcohol Control Study

Abstract: Introduction and AimsThis study examines the proportion of alcohol markets consumed in harmful drinking occasions in a range of high‐, middle‐income countries and assesses the implications of these findings for conflict of interest between alcohol producers and public health and the appropriate role of the alcohol industry in alcohol policy space.Design and MethodsCross‐sectional surveys were conducted in 10 countries as part of the International Alcohol Control study. Alcohol consumption was measured using lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…It has been shown that the alcohol industry is dependent on harmful drinking to protect its profits, and targets heavier consumers [42,43]. There is also evidence in these case studies of advertising specifically aiming to recruit heavy drinkers, as in these three examples: “If Miller Lite was to be a large profitable brand we had to attract these young heavy drinkers” .(Miller Lite, 2004 [44]) “…Campari needed to achieve a more stable and democratic base.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the alcohol industry is dependent on harmful drinking to protect its profits, and targets heavier consumers [42,43]. There is also evidence in these case studies of advertising specifically aiming to recruit heavy drinkers, as in these three examples: “If Miller Lite was to be a large profitable brand we had to attract these young heavy drinkers” .(Miller Lite, 2004 [44]) “…Campari needed to achieve a more stable and democratic base.…”
Section: Resultsmentioning
confidence: 99%
“…While in other IAC countries less than 70% of the absolute alcohol was consumed during heavy drinking occasions (e.g., Mongolia and Thailand reported 62% and St. Kitts and Nevis reported 57%), 93% of the absolute alcohol was consumed during heavy drinking occasions in Tshwane, South Africa [ 33 ]. South Africa’s political and economic history history, and the associated demographic nuances all provide clues to understanding this difference.…”
Section: Discussionmentioning
confidence: 99%
“…[11] A recent general population survey in one metropolitan area in the country, Tshwane, found that over 90% of the consumption of absolute alcohol there took place during heavy drinking occasions, defined as 8 drinks of 15 mL (12 g) for men and 6 drinks for women. [12] However, fairly little is known about the drinking behaviours of patients on ART in SA, [13] including in the Tshwane metropole in Gauteng Province. One cross-sectional survey, conducted in two HIV clinics in Tshwane, found that the Alcohol Use Disorders Identification Test (AUDIT) [14] scores of half the male and threequarters of the female drinkers were indicative of hazardous or harmful drinking.…”
Section: Researchmentioning
confidence: 99%